2018
DOI: 10.1063/1.5045727
|View full text |Cite
|
Sign up to set email alerts
|

Coupling quantum emitters in WSe2 monolayers to a metal-insulator-metal waveguide

Abstract: Coupling single photon emitters to surface plasmons provides a versatile ground for on chip quantum photonics. However, achieving good coupling efficiency requires precise alignment of both the position and dipole orientation of the emitter relative to the plasmonic mode. We demonstrate coupling of single emitters in the 2-D semiconductor, WSe2 self-aligned with propagating surface plasmon polaritons in silver-air-silver, metal-insulator-metal waveguides. The waveguide produces strain induced defects in the mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…14 This opens opportunities for coupling and/or energy routing between SPE sites in 2D semiconductors for potential applications such as on-chip quantum light sources. [15][16][17] In addition, metal nanostructures can lead to enhanced Purcell factors resulting in increased single-photon emission rates. 9,18 As such, it is natural to imagine interfacing 2D semiconductor SPEs with metals to advance quantum and optical processing technology.…”
Section: Introductionmentioning
confidence: 99%
“…14 This opens opportunities for coupling and/or energy routing between SPE sites in 2D semiconductors for potential applications such as on-chip quantum light sources. [15][16][17] In addition, metal nanostructures can lead to enhanced Purcell factors resulting in increased single-photon emission rates. 9,18 As such, it is natural to imagine interfacing 2D semiconductor SPEs with metals to advance quantum and optical processing technology.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these in-plane com-ponents, coupling efficiency is increased effectively. As realized by Subhojit Dutta et al [40] a coupled system of propagating surface plasmons in metal insulator metal waveguide (silver-air-silver) to single photon emitters in W Se 2 (Fig. 8(c)).…”
Section: W Se 2 Monolayer Given By = Hmentioning
confidence: 95%
“…[316] On-chip quantum emitters based on WSe 2 integrated with the metal waveguide were also demonstrated. [317,318] However, the majority of quantum emitters based on TMDCs are only working at cryogenic temperatures. Recent studies indicated that h-BN was an alternative material for room-temperature quantum emitters.…”
Section: Quantum Emittersmentioning
confidence: 99%